PEMBUATAN BUKU SAKU SEBAGAI MEDIA PEMBELAJARAN PADA MATERI JAMUR KELAS X SMA - Anjelita, Ria; Syamswisna, Syamswisna; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe purpose of this study was to determine the feasibility of a pocket book as a medium of learning on mushroom material of at the tenth grade of senior high school. This research was a qualitative research with descriptive method. Pocket book made as a medium of learning using double glossy paper side with a length of 13 cm and 9.2 cm wide. The pocket book consists of cover, introduction, table of contents, contents, bibliography and attachments. The pocket book was validated by five validators consisting of two lecturers of Biology Education Program, Faculty of Education Tanjungpura University and one of biology teacher at SMA Taruna Bumi Khatulistiwa, one biology teacher at SMA Kristen Maranatha and one of biology teacher of SMAN 1 Sungai Ambawang. Based on the results of media validation analysis that has been given by the five validators, then obtained the average total validation is 3.76 (valid) which means pocket book media worthy of use as a medium of learning on mushroom material tenth grade of senior high school.Â Keywords : medium of learning, mushroom, pocket bookÂ